Impact of Educational Activity Formats, Online or In-Person, on the Intention of Medical Specialists to Adopt a Clinical Behaviour: A Comparative Study - Gloria Ayivi-Vinz; Martin Tremblay; Souleymane Gadio; Suélène Georgina Dofara; Sam J Daniel; Denis Talbot; France Légaré (Taylor & Francis Group, 2024)
COVID-19 accelerated continuing professional development (CPD) delivered online. We aimed to compare the impact of in-person versus online CPD courses on medical specialists' behavioural intentions and subsequent behaviour. In this comparative before-and-after study, medical specialists attended in-person courses on nine clinical topics. A second group attended an adapted online version of these courses. Behavioural intention and its psychosocial determinants were measured before and immediately after the courses. Behaviour change was measured six months later. Generalised estimating equation (GEE) models were used to compare the impact of course formats. A total of 82/206 in-person registrants (mean age: 52±10 years; 50% men) and 318/506 on-line registrants (mean age: 49±12 years; men: 63%) participated. Mean intention before in-person courses was 5.99±1.31 and 6.43±0.80 afterwards (average intention gain 0.44, CI: 0.16-0.74; p=0.003); mean intention before online courses was 5.53±1.62 and 5.98±1.40 afterwards (average intention gain of 0.45, CI: 0.30-0.58; p<0.0001). Difference in intention gain between groups was not statistically significant. Behaviour reported six months later was not significantly associated with post-course intention in either group. However, the intention difference increased significantly among those who said they had adopted the targeted behaviour (paired wilcoxon test: n = 40 and p-value=0.002) while it did not increase significantly in the group of those who had not adopted a targeted behaviour (paired wilcoxon test: n = 16 and p-value=0.223).In conclusion, the increase in intention of specialists after CPD courses was similar whether the course was in-person or online. Also, an increase in intention in both groups signalled more likelihood of adoption.